Determination of nitrofuran residues in milk by LC/MS/MS and assessment of human health risks in Ankara region, Turkey - Ozdemir, O; Ince, S (Journal of the Hellenic Veterinary Medical Society, 2025)
Nitrofurans (NFs) are commonly used medicines for bacteria and parasites in animal diseases. Their residues in food products have mutagenic and carcinogenic effects on humans. In this study, we investigated the presence of NF metabolites which are 3 amino 2 oxazolidinone (AOZ), semicarbazide (SEM), 5 methylemorpholino 3 amino 2 oxazolidinone (AMOZ), and 1 aminohydantoin (AHD) in raw cow milk and assessment of human health risks in the region of Ankara, Turkey. End of the result showed that the linearity, recovery, and other validation parameters obtained by high-performance liquid chromatography with tandem mass spectrometry (LC/MS/MS) analyzing milk samples were at the required levels for the analysis. Also, cow raw milk instances were taken from farms in Ankara province and were analyzed by LC/MS/MS. End of the sample analyses, NFs were not found in cow raw milk instances. In conclusion, NF metabolites were good determined in milk by LC/MS/MS and milk offered for consumption does not pose a risk to consumer health for NFs.